Population ecology of the planktonic shrimp lucifer faxoni borradaile, 1915 (crustacea, sergestoidea, luciferidae) of the southeastern coast of brazil - Teodoro, Sarah S. A.; Negreiros Fransozo, Maria L.; Lopes, Mateus; Simões, Sabrina; Costa, Rogério Caetano da [UNESP] (My University, 2012)
Luciferid shrimps have short life spans and a rapid turnover of generations, engage in sequential spawning, and protect their eggs during incubation. This study investigates the ecology of Lucifer faxoni Borradaile, 1915 in the littoral zone, Ubatuba region, São Paulo. Sampling was conducted monthly from July 2005 to December 2006 using a Renfro net trawled over a distance of 50 m for a total sampling effort of 50 m² at each station. Nine stations were sampled, ranging from 1 to 15 m deep. Three stations each were grouped into zones 1, 2 and 3 (Z1, Z2 and Z3). Monthly values of salinity, temperature and rainfall were recorded at each station. The pre-buccal somite length (SL) of each specimen was measured. The results showed that in shallower zones (Z1 and Z2), 6306 individuals were captured, whereas in the deeper zone (Z3), 3808 specimens were captured, but no significant differences in SL was detected between the specimens from Z1 and Z2 and those from Z3 (ANOVA, p=0.25). The abundance of shrimps did not differ significantly between seasons (Tukey’s test, p=0.02) except in the spring. The sex ratio differed significantly over the seasons (χ², p<0.05). The results were closely associated with environmental factors with respect to the spatial and seasonal distribution of L. faxoni. Rainfall affected salinity directly, and contributed to the displacement of these shrimps to deeper areas.

Este estudo analisa a ecologia de Lucifer faxoni Borradaile, 1915 em Ubatuba, São Paulo. Os indivíduos foram coletados mensalmente de julho de 2005 a dezembro de 2006, com uma rede de Renfro, arrastada por uma distância de 50 m, totalizando um esforço amostral de 50 m² em cada ponto de coleta. Nove pontos foram amostrados, variando de 1 a 15 m de profundidade. Cada 3 pontos foram agrupados em 3 zonas (Z1, Z2 e Z3). Os valores de salinidade, temperatura e pluviosidade foram registrados mensalmente em cada transecto. Os espécimes foram medidos quanto ao comprimento do somito pré-bucal (SL). Os resultados mostram que nas zonas mais rasas (Z1 e Z2) foram coletados 6306 indivíduos, enquanto que na mais profunda (Z3) obteve-se 3808 espécimes, não havendo diferença estatística entre as zonas (ANOVA, p=0.25). A abundância não diferiu estatisticamente entre as estações do ano (Tukey, p=0.02), exceto para a primavera. Em todas as estações amostradas, o sex ratio diferiu estatisticamente (χ², p< 0.05). Os fatores ambientais aqui analisados apresentaram relação estreita com a distribuição espaço-temporal de L. faxoni. A pluviosidade influenciou diretamente a salinidade, que provocou o deslocamento dos camarões L. faxoni para áreas mais profundas.
Keywords: Abundance; Population structure; Ecologic distribution; South Atlantic; Decapoda; Abundância; Estrutura populacional; Distribuição ecológica; Atlântico Sul; Decapoda